Przyczynowość hipotetyczna. Problematyka ustalenia zakresu odpowiedzialności deliktowej w sytuacji wystąpienia tak zwanej przyczyny rezerwowej causa superveniens - Borys, Adrian (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The study presents the problems of hypothetical causation from the point of view of proximate cause and determining the extent of damage. The paper presents the views of the doctrine, both allowing the possibility of taking into account the reserve reason causa superveniens when determining the extent of damage, as well as denying such a possibility. The issue of the reserve reason as a factor affecting the extent of damage was presented from the perspective of the objective method and the differential method of determining the extent of damage. The author has shown that determining the extent of damage only by means of the method differentially leads to a result contrary to the social axiological assessment, which can’t be considered binding. The author negated domination of the differential method. However, doesn’t contradict the dynamic character of the damage. Noting the problem of development damage and liability for lost profits, the author agrees to the position according to which the extent of damage determined by the objective method — constituting the minimum extent of damage — should be corrected using the differential method. Therefore, reserve reason causa superveniens can’t lead to a reduction in the scope of the obligation to repair the damage by the entity responsible for the basic event.
Keywords: liability for tort; reserve reason causa superveniens; hypothetical causality; dynamic concept of damage; objective method of determining damages; differential method of determining damages; principle of full compensation